Thermally stimulated current and space charge limited current mechanism in film of the gold/zinc oxide/gold type - Caglar, Yasemin; Caglar, Mujdat; Ilican, Saliha; Yakuphanoğlu, Fahrettin (Elsevier, 2007)
The thermally stimulated current (TSC) and space charge limited current (SCLC) properties of n-type spray pyrolyzed ZnO thin film were investigated using TSC and current-voltage measurements. TSC measurements of the n-type film revealed the presence of one peak. The results of the characteristic parameters of the peak are T-max = 179.6 K, peak current = 9.305 x 10(-6) A. The values of the capture cross-section of the trap S-t and attempt to escape frequency nu of a trapped electron for the sample were found to be 6.99 x 10(-30) cm(2) and 2.783 x 10(-4) s(-1), respectively. The activation energy of the trap was found to be 0.00318 +/- 1.43 x 10(-4) eV. The observed trap level allows TSC. The current-voltage characteristic at 10K shows ohmic and space charge limited current regions (SCLC). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: thermally stimulated current; space charge limited current; ZnO